Effects of high-carbohydrate versus mixed-macronutrient meals on female soccer physiology and performance - Wynne, J. L.; Ehlert, A. M.; Wilson, P. B. (European Journal of Applied Physiology, 2021)
Purpose: Athletes are often told to minimize intakes of fiber, fat, and protein in pre-competition meals to avoid gut distress, but this guidance is based on scant direct evidence. This study evaluated the physiological and perceptual effects of pre-competition mixed-macronutrient (MM) and high-carbohydrate (HCHO) meals in collegiate female soccer players. Methods: Fifteen players participated in this randomized, investigator-blinded, crossover study involving two ~ 1000-kcal meals (HCHO and MM) consumed 4 h prior to 70-min scrimmages. Assessments included global positioning system (GPS) tracking, heart rate (HR), perceived exertion (RPE), ratings of fatigue (ROF), gut symptoms, and perceptions of satiety, hunger, and fullness. Differences between conditions for HR, RPE, ROF, and gut symptoms were evaluated with Wilcoxon signed-rank tests. GPS data and hunger, satiety, and fullness scores were compared using within-subjects repeated measures ANOVAs. Results: No statistically significant differences were found between the conditions at any time point for HR, RPE, ROF, or gut symptoms. Significant time effects were found for two GPS variables (total distance covered and high-speed running), indicating that participants covered less distance during the second half of the scrimmages in comparison to the first half. However, there were no significant condition or condition × time interactions for GPS data. Finally, there were no condition or condition × time interactions for hunger, fullness, and satiety, though significant time effects were observed. Conclusion: A MM meal consumed 4 h prior to 70 min of soccer competition does not increase gut symptoms and can be similarly ergogenic as a HCHO meal.